2015
DOI: 10.1186/s12887-015-0341-8
|View full text |Cite
|
Sign up to set email alerts
|

Social, dietary and clinical correlates of oedema in children with severe acute malnutrition: a cross-sectional study

Abstract: BackgroundSevere acute malnutrition is a serious public health problem, and a challenge to clinicians. Why some children with malnutrition develop oedema (kwashiorkor) is not well understood. The objective of this study was to investigate socio-demographic, dietary and clinical correlates of oedema, in children hospitalised with severe acute malnutrition.MethodsWe recruited children with severe acute malnutrition admitted to Mulago Hospital, Uganda. Data was collected using questionnaires, clinical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
“…We did a stratifi ed analysis of paediatric HIV prevalence in southern and eastern Africa (20 studies) 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27]28,29 versus that in west and central Africa (four). 9,23,28,31 Paediatric HIV prevalence across contexts in southern and eastern Africa was 17·8% (95% CI 12·8-22·7) and prevalence in west and central Africa was 9·8% (95% CI 4·2-15·3).…”
Section: Resultsmentioning
confidence: 99%
“…BED was the only skin sign exclusively observed among oedematous patients in our cohort, but there was a strong tendency also pointing towards LSC and ISC as oedema‐specific signs. Other details on oedema and its relation to clinical characteristics in the study group, has been presented in another article related to the FeedSAM study …”
Section: Resultsmentioning
confidence: 99%
“…Other details on oedema and its relation to clinical characteristics in the study group, has been presented in another article related to the FeedSAM study. 16 Telogenic effluvium The children in our cohort had various grades of telogenic effluvium combined with depigmentation and/or straightening of the curls. The flag sign, where the nutritional status of a child over time is reflected through light bands in the hair, was only observed in four cases.…”
Section: Characterization Of Skin Manifestations In Sammentioning
confidence: 99%
“…Although various explanations are given for pathophysiology of oedema in malnutrition, mortality still remains high in children with oedematous malnutrition, but little is known about burden of oedematous malnutrition and few large-scale surveys are yet to measure it. 8,9 This study was intended to study the clinical correlates with severe acute malnutrition and to know the incidence of oedematous malnutrition among children with severe acute malnutrition.…”
mentioning
confidence: 99%